Predicting dietary and fluid adherence in hemodialysis : an application and extension of the theory of planned behaviour - Fincham, Dylan Shaun (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MA (Psychology))--University of Stellenbosch, 2005.